NILAI-NILAI KEARIFAN LOKAL DALAM PARIBASA URANG BANJAR (The Values of Local Wisdom in Paribasa Urang Banjar) - Siti Jamzaroh Wahdanie R Siti Alfa A (Balai Bahasa Sumatra Barat, 2017)
Cultural values are inherited in various forms, one of them in a proverb. Banjar society inherites theirs cultural values through expressions and proverbs. This study aims to (1) describe the relationship of cultural values and behavior; (2) describe the value system, and (3) characterize the cultural values in terms of universality. The source of this research datais a book entitled Paribasa Urang Banjar. This research is conducted in three stages, namely data collecting, data processing, and data analyzing. The results showed that Paribasa Urang Banjar contains the values of local wisdom that include (1) Cultural values related to one’s behavior, such as attitude and outlook of life and strong determination. (2) Cultural valuesrelated to the value system, such as, family norms, economic / commercial norms, and social institutions. (3) Cultural values related to universality, such as goodness, justice, and science. The conclusion of this research is that Banjar society is a society that also inherites theirs cultural values through proverbs.